2023
DOI: 10.3389/fmed.2023.1185769
|View full text |Cite
|
Sign up to set email alerts
|

Dismissal informs the priorities of endometriosis patients in New Zealand

Abstract: IntroductionEndometriosis is a common condition with average delays to diagnosis in New Zealand of almost 9 years.MethodsIn total, 50 endometriosis patients participated in anonymous, asynchronous, online group discussions about their priorities, and their experiences with the development of symptoms, seeking a diagnosis, and receiving appropriate treatment.ResultsHigher subsidy of care was the top change endometriosis patients wanted, followed by more research funding. When asked to choose whether research sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 55 publications
1
13
0
1
Order By: Relevance
“…That study identified an average delay from symptom onset to surgically confirmed diagnosis of 8.6 years [2], consistent with a prior New Zealand report [7]. It was also identified that experiences of dismissal or doubt contributed significantly to the diagnostic delay (reports of dismissal increased the average delay from 4.6 ± 3.4 years to 9.0 ± 5.2 years (p = 0.0017)) [9]. Of available treatment methods, those most commonly prescribed by clinicians, such as hormone-based medications, were rarely viewed as effective by users [2].…”
Section: Introductionsupporting
confidence: 85%
See 3 more Smart Citations
“…That study identified an average delay from symptom onset to surgically confirmed diagnosis of 8.6 years [2], consistent with a prior New Zealand report [7]. It was also identified that experiences of dismissal or doubt contributed significantly to the diagnostic delay (reports of dismissal increased the average delay from 4.6 ± 3.4 years to 9.0 ± 5.2 years (p = 0.0017)) [9]. Of available treatment methods, those most commonly prescribed by clinicians, such as hormone-based medications, were rarely viewed as effective by users [2].…”
Section: Introductionsupporting
confidence: 85%
“…In this study, participants took part in anonymous, asynchronous online text-based discussions on boards hosted on VisionsLive Ltd., (London, United Kingdom). The questionnaire from a 2022 qualitative study conducted with endometriosis patients in New Zealand [2,9] was adapted and streamlined for a cohort comprised of Māori and Pasifika patients to ensure that both cultural appropriateness and experiences unique to these cohorts would be addressed. The redesigned questionnaire was assessed by two Māori researchers (one of which is a person with endometriosis) and two Pasifika medical practitioners to ensure question wording and intent were valid for this context.…”
Section: Discussion Board Designmentioning
confidence: 99%
See 2 more Smart Citations
“…For this, better education around menstrual health and what is ‘normal’ is vital. The impact of lack of knowledge of what is normal hugely impacts healthcare seeking and care received [56] and general lack of societal acceptance leads to loss of social connection [57].…”
Section: Future Workmentioning
confidence: 99%